The Marine Fisheries in Bulgaria's Exclusive Economic Zone, 1950–2013 - Keskin, Çetin; Ulman, Aylin; Zylich, Kyrstn; Raykov, Violin; Daskalov, Georgi M.; Pauly, Daniel; Zeller, Dirk (Frontiers in Marine Science, 2017)
This study presents a reconstruction of the total catch of Bulgarian marine fisheries in the Bulgarian Exclusive Economic Zone for the time period 1950–2013, including previously unreported landings, discards, recreational and subsistence catches. The landings data officially reported by Bulgaria to the Food and Agriculture Organization of the United Nations for the Mediterranean and Black Seas (FAO Area 37) were revised in line with all available information. The reconstructed total catch for 1950–2013 was 1.7 times the (adjusted) baseline data reported by Bulgaria to FAO and 1.5 times the unadjusted data as reported by FAO. This study revealed major deficiencies in the officially reported Bulgarian catch data, foremost the large amount of unreported industrial catches, especially for the last two decades. The exclusion of some fisheries sectors, notably the absence of data on the subsistence and recreational fisheries in reported data are also noteworthy.